Autonomy Benefits and Risks of Assistive Technologies for Persons With Intellectual and Developmental Disabilities - O'Brolcháin, Fiachra (Frontiers in Public Health, 2018)
This paper explores the ways in which assistive technologies (ATs) can both promote and undermine the autonomy of Persons with Intellectual and Developmental Disabilities (PIDD). Following an initial discussion of ATs for PIDD, I examine the specific issues of autonomy for PIDD. I outline the ways in which ATs can boost autonomy, of PIDD, focusing on knowledge, authenticity, and liberty. Following that I suggest that ATs are not necessarily beneficial in terms of autonomy and examine ways that they might be used to undermine the autonomy of PIDD, specifically the categories of knowledge, authenticity, and liberty. I conclude by suggesting that the development of ATs requires ethical oversight.